The Role of Orgniational comunication in the Production Process at Sonatrach Company A Field Stuay at Sy - Abederrahane Houam; Hadjadj Madani (جامعة عمار ثليجي الاغواط, 2024)
الملخص Summary in arabic هدفتهذهالدراسةإلى تحليلدورالاتصالالتنظيميفيسيرورةعمليةالإنتاجبشركةسوناطراكحاسيرملDP،معالتركيزعلىكيفيةتأثيرهذاالاتصالفيبناءالتفاعلوالتناغمداخلفرقالعملبقسمالإنتاج،وتأثيرذلك على جودة المنتج النهائي،وكذلكفيفهمموظفيالقسملأهدافالشركة. فيبدايةالدراسة،تماستعراضأهميةالاتصالالتنظيميومفهومهوكل ما يتعلق به من الناحية النظرية، و فهم دورهكعنصرأساسيفينجاحالمؤسسات،وخاصةفيالشركاتالكبرىمثلسوناطراك،التيتعتمدعلىالتنسيقالدقيقبينمختلفالأقساموالفرقلضمانسيرعمليةالإنتاجبكفاءة. كما تم دراسة مفهوم الإنتاج من النواحي الفلسفية و الاقتصادية و الاجتماعية ، بعدها تمجمعالبياناتخلال الدراسة الميدانية بقسم الإنتاج بحاسي رمل ، منخلالاستبياناتموزعةعلىعينةمنالموظفينبالمركب الصناعي ،وتمتحليلالنتائجلتوضيحدورالاتصالالتنظيميفيتعزيزالأداءالوظيفيوتحقيقالأهدافالإنتاجية ، مع عمل مقابلات مع المسؤولين داخل القطاع لتدعيم نتائج الاستبيان ، حيث أظهرتالنتائجأنهناكتأثيراًإيجابياًقوياًللاتصالالتنظيميعلىفهمالموظفينلأهدافالشركة و توقعاتها لمستوى جودة المنتج النهائي لعملية الإنتاج ، حيثيساعدالتواصلالفعّالفينقلالرؤيةوالمهامبوضوح،ممايسهمفيزيادةالتزامالموظفينورفعمستوىأدائهم ، كماأوضحتالدراسةأنوجودتوجيهاتواضحةودعمفنيمنتظممنالإدارةيعززمنقدرةالموظفينعلىالتعاملمعالتحدياتاليوميةوتحقيقالتناغمبينأفرادفريقالعمل. وبالمثل،فإنتشجيعالتواصلالمفتوحوالشفافبينالأقسامالمختلفةيساهمفيتحسينبيئةالعملويقللمنالأخطاءالإنتاجية. فيالنهاية،تمتقديممجموعةمنالتوصياتلتعزيزالاتصالالتنظيميفيشركةسوناطراك،منبينها: - ضرورةتنظيمبرامجتدريبيةلتطويرمهاراتالتواصلبينالموظفين. - توفيرالأدواتالتقنيةاللازمة،وتشجيعالاجتماعاتالدوريةلمناقشةالتحسينات. - تقديمالدعمالنفسيوالفنيلتعزيزبيئةالعمل. الكلمات المفتاحية : الإتصال التنظيمي 》الإنتاج 》مؤسسة سوناطراك Summary of the memo This study aimed to analyse the role of organizational communication in the production process at Sonatrach Hassi Rmel DP, focusing on how this communication affects interaction and harmony within the production department teams, its impact on the final product quality, and the employees’ understanding of the company’s goals. At the outset, the study also reviewed the importance and concept of organizational communication from a theoretical perspective, understanding its role as a fundamental element in the success of institutions, particularly large companies like Sonatrach, which rely on precise coordination between various departments and teams to ensure the efficient flow of the production process. Additionally, the study explored the concept of production from philosophical, economic, and social perspectives. Following this was thefield groundwork, data was collected through a field study in the production department at Hassi Rmel. This involved distributing questionnaires to a sample of employees at the industrial complex and conducting interviews with sector officials to support the survey findings. The results indicated a strong positive impact of organizational communication on employees’ understanding of the company’s goals and expectations on the final product quality. Effective communication helps in clearly conveying the vision and tasks, which contributes to increased employee commitment and improved performance.
onatrach company - HASSI r'mel DP -